Participatory democratic management: A challenge to educational institutions of Angola (Revista Contexto & Educação, 2026)
This article aims to understand the challenges of implementing participatory democratic management in educational institutions in Angola, analyzing the role of the school manager in mobilizing the educational community for active participation and in promoting quality learning. Participatory democratic management, by involving all members of the educational community in the decision-making process, aims to overcome the authoritarian and centralizing practices still present in Angolan schools. This is a qualitative study of bibliographic and documentary nature, with an intentional selection of literature relevant to the topic. The study concludes that, despite the formal recognition of democracy in legislation, the centralization of power and resistance to change hinder the effective implementation of this guiding principle. For its effectiveness, the adoption of leadership practices that promote collaboration and decentralization of curricular decisions is essential.
Keywords: Democratic management; School leadership; Decentralization; Participation; Angola